(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2019)
In the theories and approaches of development, it has not been considered that religion has a vision of development as such. The article seeks to define the conceptual elements that demonstrate that Roman Catholic Apostolic Christianity, specifically in its Social Doctrine has a vision of development; for that propose, we will describe in a general way, the main theories and approaches in the social sciences, the main notions of the Catholic vision, and the possible dialogue between both. The study concludes that the Catholic vision can contribute elements for the debate of the development in the academicphilosophical plane, and as such, can dialogue with some of the secular visions, especially with the capabilities approach.